Jejunal intussusception caused by metastatic scalp melanoma with synchronous gallbladder involvement: A case report - Handaya, Adeodatus Yuda; Aditya, Azriel Farrel Kresna; Tianty, Belvia Adelaida Maia (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2026)
Adult jejunal intussusception due to metastatic melanoma originating from a scalp lesion represents an uncommon clinical entity. Despite being a relatively rare form of skin cancer, melanoma is known for its aggressive behaviour and high metastatic capacity. Although metastases to the gallbladder are infrequent, melanoma is considered the most prevalent source of secondary tumours in this organ. Gallbladder metastases often resemble asymptomatic polyps, solid lesions, or cholecystitis. These lesions are increasingly identified as incidental findings due to the advances in medical imaging. In this case, multislice computed tomography (MSCT) served as the primary diagnostic modality, identifying both the jejunal intussusception with an intraluminal lead point and multiple gallbladder polyps. We report a clinical course of a 65-year-old man with a history of scalp melanoma who presented with gastrointestinal symptoms. The patient underwent exploratory laparotomy, segmental resection of the jejunum with primary anastomosis, and cholecystectomy. Histopathological findings confirmed the diagnosis of metastatic melanoma involving the resected tissues. This report emphasizes an imperative of continuous monitoring and an early detection in melanoma survivors, as well as a critical role of timely surgical intervention in managing metastatic manifestations.